2013
DOI: 10.1155/2013/795072
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulatory Role of an Ayurvedic Formulation on Imbalanced Immunometabolics during Inflammatory Responses of Obesity and Prediabetic Disease

Abstract: Kal-1 is a polyherbal decoction of seven different natural ingredients, traditionally used in controlling sugar levels, inflammatory conditions particularly regulating metabolic and immunoinflammatory balance which are the major factors involved in obesity and related diseases. In the present study, we aimed to investigate the effect of Kal-1 (an abbreviation derived from the procuring source) on diet-induced obesity and type II diabetes using C57BL/6J mice as a model. The present study was performed with two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(22 citation statements)
references
References 35 publications
(44 reference statements)
3
18
0
Order By: Relevance
“…HFHSD fed mice were then further separated into subgroups that either received no additional treatment, or were treated with different doses of the Ayurvedic formulation KAL-1. Experimental results, based on the physiological parameters like body weight, blood glucose levels and cytokine profiles, confirmed the earlier findings [ 6 ] that KAL-1 prevented mice from both obesity and diabetes. Thus, by comparing between the different groups, our experimental system offered an opportunity to identify disease-specific perturbations in gene expression in different tissues.…”
Section: Introductionsupporting
confidence: 86%
See 1 more Smart Citation
“…HFHSD fed mice were then further separated into subgroups that either received no additional treatment, or were treated with different doses of the Ayurvedic formulation KAL-1. Experimental results, based on the physiological parameters like body weight, blood glucose levels and cytokine profiles, confirmed the earlier findings [ 6 ] that KAL-1 prevented mice from both obesity and diabetes. Thus, by comparing between the different groups, our experimental system offered an opportunity to identify disease-specific perturbations in gene expression in different tissues.…”
Section: Introductionsupporting
confidence: 86%
“…al . [ 6 ] showed that KAL-1, a formulation derived from Ayurveda which a system of Indian Traditional Medicine, was extremely effective at suppressing the development of diet-induced obesity in the mouse model. Importantly, development of other related disorders of type 2 diabetes and systemic inflammation was also prevented.…”
Section: Introductionmentioning
confidence: 99%
“…Then, microarray experiment was performed on tissue samples and after suitable normalization of the signal intensities of each probe using Agilent Genespring GX software, three values of log fold change for the control sample and the treated sample were obtained for each probe and at each time for each tissue. Further details of the experiment are given in [17]. …”
Section: Methodsmentioning
confidence: 99%
“…The cancer dataset was taken from GDS3716. The liver microarray dataset used to show application of the algorithm was taken from [17]. This data is also available in from the NCBI repository under GEO accession number GSE63175.…”
Section: Acknowledgementsmentioning
confidence: 99%
“…Around the world millions of people are using traditional medicines and formulations based on Ayurveda as front line medicinal product for diabetes. 7 Ayurveda, which means "science of life", is a traditional Indian system of medicine that has been documented and practiced since 3000 B.C. 8 It is an alternative form of medicine, composed of elements of physiology, pathology, pharmacology, material medica and surgery.…”
Section: It Ismentioning
confidence: 99%